2016
DOI: 10.5194/nhess-16-2391-2016
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of uncertainties and skill in forecasts of winter storm losses

Abstract: Abstract. This paper describes an approach to derive probabilistic predictions of local winter storm damage occurrences from a global medium-range ensemble prediction system (EPS). Predictions of storm damage occurrences are subject to large uncertainty due to meteorological forecast uncertainty (typically addressed by means of ensemble predictions) and uncertainties in modelling weather impacts. The latter uncertainty arises from the fact that local vulnerabilities are not known in sufficient detail to allow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…This is done by adapting WiTRACK-a scheme proven to be successful for objectively identifying damaging windstorms associated with extra-tropical cyclones (e.g. Leckebusch et al 2008, Nissen et al 2010, Pardowitz et al 2016-for applicability to damaging TCs. The basic approach of this detection method is based on the assumption that infrastructure and building standards are usually adapted to the local wind climatology and damages typically occur for wind speeds beyond a threshold associated with a certain return period, that is a specific quantile of the local wind climatology.…”
Section: Introductionmentioning
confidence: 99%
“…This is done by adapting WiTRACK-a scheme proven to be successful for objectively identifying damaging windstorms associated with extra-tropical cyclones (e.g. Leckebusch et al 2008, Nissen et al 2010, Pardowitz et al 2016-for applicability to damaging TCs. The basic approach of this detection method is based on the assumption that infrastructure and building standards are usually adapted to the local wind climatology and damages typically occur for wind speeds beyond a threshold associated with a certain return period, that is a specific quantile of the local wind climatology.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a potential for warnings but with possible false alarms, as already noted by Lalaurette (2003). The use of EFI and SOT thus requires an appropriate balance between hit and false alarm rates (Petroliagis and Pinson, 2014;Boisserie et al, 2016).…”
Section: Extreme Forecast Index (Efi) and Shift Of Tails (Sot)mentioning
confidence: 82%
“…As noted by Lalaurette (2003), the EFI gives useful warnings of extreme events but also frequent false alarms. Petroliagis and Pinson (2014) therefore suggested the use of an optimal threshold to balance between hit rate (H ) and false alarm rate (F ), a lower or higher thresh- old increasing or decreasing both H and F . Boisserie et al (2016) further suggested to maximise the Heidke skill score (HSS; Heidke, 1926) to define the optimal threshold.…”
Section: Efi and Sot For Gusts Above The 98th Percentilementioning
confidence: 99%
See 1 more Smart Citation
“…Regional models are required to represent mesoscale features such as sting jets or convection embedded in the cold front, while the accurate representation of wind gusts stays beyond the resolution of operational models and relies on large-eddy simulations or observations at the turbulent scale. Alternatively, dynamical and statistical downscaling can be combined to obtain skillful forecasts at the local level, as demonstrated by Pardowitz et al (2016) for storm losses, who further took both meteorological and damage model uncertainties into account. These different approaches shall be considered to allow advances in the predictability of severe European winter storms.…”
mentioning
confidence: 99%